Nivolumab plus rucaparib for metastatic castration-resistant prostate cancer: results from the phase 2 CheckMate 9KD trial - Fizazi, Karim; Retz, Margitta; Petrylak, Daniel P.; Goh, Jeffrey C.; Perez-Gracia, Jose; Lacombe, Louis; Zschäbitz, Stefanie; Burotto, Mauricio; Mahammedi, Hakim; Gravis, Gwenaelle; Bastos, Diogo Assed; McCune, Steven L.; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background CheckMate 9KD (NCT03338790) is a non-randomized, multicohort, phase 2 trial of nivolumab plus other anticancer treatments for metastatic castration-resistant prostate cancer (mCRPC). We report results from cohorts A1 and A2 of CheckMate 9KD, specifically evaluating nivolumab plus rucaparib.
Gesehen am 22.11.2022